EVALUATING THE BLOOD-SPARING EFFICACY AND SAFETY OF TRANEXAMIC ACID IN TOTAL KNEE ARTHROPLASTY - R, Ramya; LEENA RANJINI V; HARISIVANANDAN M (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Tranexamic acid (TXA) is an antifibrinolytic agent that effectively reduces bleeding both during and after surgery. The purpose of our study was to assess the effectiveness and safety of TXA use in reducing blood loss in uncomplicated primary total knee arthroplasty (TKA) without complications. Methods: This is a prospective, open-label, comparative study that includes patients who are undergoing unilateral primary TKA. The patients were divided into two groups: Group I, which is a control group, did not receive any doses of TXA, and Group II received three doses of intravenous TXA: 15 mg/kg TXA was administered 30 min before incision, followed by post-operative doses of 10 mg/kg TXA at 3 and 6 h. The primary objectives of the study were to measure the total blood loss (TBL) and Hemoglobin (Hb) drop, which were calculated preoperatively and on the third post-operative day. The secondary objectives were to determine transfusion rates, incidences of symptomatic deep vein thrombosis, and thromboembolic events (TE). Results: In this study, a total of 57 patients underwent unilateral TKA. The TBL in Group I was 861.67±167.65 mL, compared to 780.05±158.05 mL in Group II (p<0.001). The study also found that the Hb drop was significantly lower (2.78±0.36 vs. 2.3±0.37) with IV TXA. Furthermore, neither group required transfusions, nor were any thromboembolic complications noted for up to 6 months post-operation. Conclusion: Our study supports the use of TXA in TKA, as it effectively reduces perioperative blood loss, decreases the need for blood transfusions, and does not increase the risk of TE.